Adipocytokine and ghrelin levels in relation to bone mineral density in prepubertal rhythmic gymnasts entering puberty: a 3-year follow-up study - Võsoberg, K.; Tillmann, V.; Tamm, A. L.; Jürimäe, T.; Maasalu, K.; Jürimäe, J. (European Journal of Applied Physiology, 2016)
Purpose: To investigate changes in bone mineral density (BMD) in rhythmic gymnasts (RG) entering puberty and their age-matched untrained controls (UC) over the 36-month period, and associations with leptin, adiponectin and ghrelin over this period. Methods: Whole body (WB), lumbar spine (LS) and femoral neck (FN) BMD, WB bone mineral content (BMC), and leptin, adiponectin and ghrelin were measured in 35 RG and 33 UC girls at baseline and at 12-month intervals over the next 3 years. The change over the 36 months was calculated (Delta score). Results: The pubertal development over the next 36 months was slower in RG compard to UC, while there was no difference in bone age development between the groups. BMD at all sites was higher in RG in comparison with UC at every measurement point. DeltaLS BMD and DeltaFN BMD, but not DeltaWB BMD and DeltaWB BMC, were higher in RG compared with UC. None of the measured hormones at baseline or their Delta scores correlated with DeltaBMD and DeltaBMC in RG. Baseline fat free mass correlated with DeltaWB BMD and DeltaWB BMC in RG, while baseline leptin was related to DeltaWB BMC, DeltaWB BMD and DeltaLS BMD in UC. Conclusions: Measured baseline hormones and their Delta scores did not correlate with increases in bone mineral values in RG entering puberty. Although the pubertal development in RG was slower than in UC, high-intensity training appeared to increase BMD growth and counterbalance negative effects of slow pubertal develpment, lower fat mass and leptin in RG.